Al-Islām wa Fatānīyūn fī Taylānd: Taḥaddīyat al-Māḍī wa Taṭallu’āt al-Mustaqbal - A. Ghani Ya'qub (Studia Islamika, 2003)
This article presents abroad discussion on the history of lslam in Patani. This discussion, which relies heavily on local sources of information, also provides an explanation of the various factors that have influenced the formation of the Patani Muslim community's culture, including social, economic and political elements.DOI: 10.15408/sdi.v10i2.633